Rat Hippocampal Neural Stem Cell Modulation Using PDGF, VEGF, PDGF/VEGF, and BDNF - Neus Gomila Pelegri; Catherine A. Gorrie; Jerran Santos (Stem Cells International)
Neural stem cells have become the focus of many studies as they have the potential to differentiate into all three neural lineages. This may be utilised to develop new and novel ways to treat neurological conditions such as spinal cord and brain injuries, especially if the stem cells can be modulated in vivo without additional invasive surgical procedures. This research is aimed at investigating the effects of the growth factors vascular endothelial growth factor, platelet-derived growth factor, brain-derived neurotrophic factor, and vascular endothelial growth factor/platelet-derived growth factor on hippocampal-derived neural stem cells. Cell growth and differentiation were assessed using immunohistochemistry and glutaminase enzyme assay. Cells were cultured for 14 days and treated with different growth factors at two different concentrations 20 ng/mL and 100 ng/mL. At 2 weeks, cells were fixed, and immunohistochemistry was conducted to determine cellular differentiation using antibodies against GFAP, nestin, OSP, and NF200. The cell medium supernatant was also collected during treatment to determine glutaminase levels secreted by the cells as an indicator of neural differentiation. VEGF/PDGF at 100 ng/mL had the greatest influence on cellular proliferation of HNSC, which also stained positively for nestin, OSP, and NF200. In comparison, HNSC in other treatments had poorer cell health and adhesion. HNSC in all treatment groups displayed some differentiation markers and morphology, but this is most significant in the 100 ng/ml VEGF/PDGF treatment. VEGF/PDGF combination produced the optimal effect on the HNSCs inducing the differentiation pathway exhibiting oligodendrocytic and neuronal markers. This is a promising finding that should be further investigated in the brain and spinal cord injury.